The Effect of Variation of Stories' Plan Size along Height of Relatively Tall Steel Buildings on Their Seismic Behavior - Shahbazi, Fatemeh; Hosseini, Mahmood (Korean Soc Steel Construction-Kssc, 2024)
In urban environments, in many cases, buildings with unequal story plan sizes are desired, resulting in non-uniform mass/stiffness distributions along the buildings' height. In this study, three groups of 12-story steel buildings with uniform, ascending, and descending story plan size distribution (PSD) along their height, but having the same total architectural space, were investigated to determine how this distribution affects their seismic performance. First, three site conditions-stiff, medium, and soft-were considered, and all buildings were designed by considering moment frames with concentrical bracings as their lateral load-bearing systems. Then, for each site class, seven appropriate sets of accelerograms were selected, and using nonlinear time history analyses, the buildings' seismic performance levels were compared based on the formation of plastic hinges (PHs). Results show that non-uniform PSD can be quite effective on the seismic performance of buildings' structures, so that on hard and soft sites, the number of PHs exceeding the collapse prevention performance level in buildings with ascending and descending PSD, respectively, decreases by approximately 30-45% and 20-40% compared with the uniform buildings. Therefore, it is explicitly concluded that employing buildings with uniform plan sizes does not necessarily lead to a higher seismic performance level.
Keywords: Height-wise plan size distribution; Seismic response; Time history analysis; Descending/ascending/uniform plan size distribution